Diffusion model of the thermal conductivity plateau of weak solid solutions of neon in parahydrogen: 9th International Conference on Cryocrystals and Quantum Crystals Odessa, Ukraine, September 2–8, 2012 (final part) - Zholonko, N.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The diffusion kinetic of classic impurity particles has been investigated in the frame of one-dimensional two-level model and applied for the explanation of solid hydrogen thermal conductivity data with extremely low concentrations of neon impurity in samples growth at different crystallization rates in which the plateau effect was observed. The main idea is that heavy isotopic impurities could segregate into thin long chains near dislocation cores if the growth rate is slow. Neon impurity chains can persist for a long time. Such rigid linear objects ensure inelastic scattering of phonons. The diffusion coefficient of neon atoms in (p-H2)1–cNec mixtures was estimated for the experimental conditions with с = 0.0001 аt. % and с = 0.0002 аt. %.